Navigating Bureaucratic Changes: A New Public Service Perspective on Tourism and Culture Governance in Malang Regency, Indonesia - Supriyanto, Didik; Wahyudi, Sigit; Suljatmiko, Suljatmiko; Setyowati, Eka; Murliasari, Rikha; Saefudin, Arif (Journal of Governance and Public Policy, 2025)
Bureaucratic reform in Indonesia has been a key agenda since the early 21st century, focusing on enhancing efficiency, transparency, and accountability in government management. This study aims to delve into and analyse the bureaucratic reform process at the Tourism and Culture Office (TCO) of Malang Regency using the New Public Service (NPS) framework. Employing descriptive qualitative research methods, the study examines the internal and external factors influencing the effectiveness of bureaucratic reform in the agency. Data were gathered through in-depth interviews, observations, and documentation studies, with triangulation data analysis techniques ensuring the validity and reliability of the findings. The results indicate that TCO Malang Regency has successfully implemented seven NPS principles: serving citizens, prioritising the public interest, valuing citizenship over entrepreneurship, thinking strategically and acting democratically, recognising the complexity of accountability, serving rather than directing, and valuing people over productivity. Programs such as Data Request or Interview, Malang Creative Hub, and Land and Building Tax incentives for cultural heritage preservation exemplify the application of these principles. Consequently, this research significantly contributes to the understanding and development of more modern, effective, and responsive public service practices in response to community needs in Indonesia, particularly in Malang Regency.